ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN DI PT DUTA PALMA NUSANTARA SEI KUKO KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Aulia, Mimim; Kartikowati, Rr. Sri; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the problem of employee job satisfaction with the aim to determine the factors that affect employee job satisfaction. The subjects of this study were employees of PT Duta Palma Nusantara Sei Kuko, totaling 433 people, the sample selection used the Slovin formula and used purposive sampling technique with a sample of 82 respondents. The data used are primary data and secondary data with data collection techniques using questionnaires and documentation. The data analysis technique used is Multiple Linear Regression Analysis and Determination Coefficient Test which is processed through the SPSS For Windowa version 22 and Microsoft Excel program. The results of this study indicate that compensation has a significant effect on employee job satisfaction by 35.9% and the work environment has a significant effect on employee job satisfaction by 35.0% and simultaneously compensation and work environment have a significant effect on employee job satisfaction at PT Duta Palma Nusantara Sei Kuko. by 43.0%.Key Words : Job Satisfaction, Compensation, Work Environment